Testing the Construct Validity and Reliability of the Student Learning Interest Scale Using Confirmatory Factor Analysis (CFA) - Adetia Swarni; Herwin; Sujati (Postgraduate, University of Mataram, 2024)
Learning interest is one of the determining factors of student learning success. The low interest of students in learning process is caused by several problems that occur. Thus, learning interest is very important in learning progress, namely to bring out students' interest and activeness in learning. To support learning and increase students' interest in learning, teachers should not only master the material but also create interesting learning to help arouse curiosity, enjoyment and interest in learning in them. This study aims to test the validity and reliability of the construct of the developed learning interest scale. A researcher needs 250 to 500 respondents. This study involved 300 random samples of fifth grade elementary school students in Berbah District, Sleman, Yogyakarta, Indonesia. Data were analyzed with second-order confirmatory factors assisted by IBM SPSS version 26 software. This study measures the validity and reliability of elementary school students' interest in learning science. So the data analysis in this study measures validity and reliability. So this study uses second order confirmatory factor analysis (nd order CFA). The results showed that the developed learning interest scale had met the criteria of suitability, convergent validity, discriminant validity, construct reliability. Therefore, the developed scale is feasible to use.